Yield and genetic dissimilarity of sour passion fruit genotypes cultivated in the Southwestern Amazon - de Araújo, James Maciel; Neto, Romeu Carvalho Andrade; Tavella, Leonardo Barreto; Leite, Hugo Mota Ferreira; Lessa, Lauro Saraiva; de Abreu, Marcos Giovane Pedroza [UNESP] (State University of Mato Grosso do Sul, 2024)
The yield of yellow passion fruit often falls below 20% of its potential due to the use of non-recommended cultivars by producers. To address this issue, ten genotypes of Passiflora edulis Sims were introduced in the edaphoclimatic conditions of Mâncio Lima, located in the Juruá microregion, State of Acre, Brazil, to evaluate their performance and identify promising ones. A randomized complete block design was used with three replications and eight plants per plot, and the yield, and physical and chemical quality of fruits were evaluated. Data were analyzed using analysis of variance, and the means were compared using the Scott-Knott test at 5% significance. A multivariate analysis was performed to obtain the dissimilarity matrix based on the Mean Euclidean Distance, and Pearson‟s correlation analysis was used to establish the correlation network. Differences were found between genotypes and across evaluation months for the studied traits. Genotypes Acre Selection, BRS Rubi Cerrado, BRS Sol Cerrado, BRS Gigante Amarelo, FB 200, and CPAC VML x 325 showed superior agronomic performance and can be recommended for the passion fruit production system in the region.
Produtividade e dissimilaridade de genótipos de maracujazeiro-azedo cultivado no sudoeste amazônico
Keywords: Agronomic traits; Fruit quality; Passiflora edulis; Yield